Assessing the Function of Judicial Committees in Nepal: Case Study of Bhaktapur District - Bhattarai, Riya (Kathmandu School of Law Review, 2021)
The transition of Nepal from a unitary set-up to a federal system has come with a host of institutional changes that are both functional and structural in nature. The existing institutions of the State have been refurbished towards implementing the new federal constitution. All the organs of government have devolved their power to all three tiers of government to address the concerns of the citizenry. In a similar vein, Article 217 of the Constitution of Nepal (hereinafter Constitution) has revived traditional dispute settlement mechanisms to mitigate the inefficiencies of the formal legal system by envisioning judicial committees that devolve judicial power to the local level. This paper is an attempt to analyze whether these judicial committees are functioning effectively and explore the challenges that they face in exercising their judicial power.